2021
DOI: 10.3390/jcm10184134
|View full text |Cite
|
Sign up to set email alerts
|

The Aggregate Index of Systemic Inflammation (AISI): A Novel Prognostic Biomarker in Idiopathic Pulmonary Fibrosis

Abstract: Variable patterns of disease progression are typically observed in patients with idiopathic pulmonary fibrosis (IPF). We sought to determine the prognostic capacity of blood cell count indexes, derived from routine complete blood cell (CBC) count, in a cohort of IPF patients. The neutrophil-to-lymphocyte ratio (NLR), derived neutrophil-to-lymphocyte ratio (dNLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), systemic inflammation index (SII), systemic inflammation response index (SIRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 65 publications
0
40
0
2
Order By: Relevance
“…WBC count and its derived indicators such as the neutrophil-to-lymphocyte ratio (NLR) based on the coexistence of lymphopenia and leukocytosis in the initial inflammatory response 17 , 18 , lymphocyte-to-monocyte ratio (LMR) can reflect the body’s immune status, and its decrease indicates host immune dysfunction 19 , platelet-to-lymphocyte ratio (PLR) is an inflammatory marker of immune-mediated, metabolic, prothrombotic, and neoplastic diseases 20 , have been considered as predictors of severity and prognosis of the disease although, by combining several of these parameters, the prediction can be greatly improved. Then, others more inclusive ratios such as: (i) neutrophil x monocyte-to-lymphocyte ratio (systemic inflammation response index or SIRI), which has a stronger stability than NLR and an elevated SIRI suggests increased inflammation and reduced immune response in patients 21 , 22 ; (ii) neutrophil x platelet-to-lymphocyte ratio (systemic immune-inflammation index or SII) with poor prognosis when augmented 23 , 24 and (iii) neutrophil x monocyte x platelet-to-lymphocyte ratio (aggregate index of systemic inflammation or AISI) 25 have been proposed as cheap and easily measurable biomarkers or indicators to improve the diagnosis/prognosis in numerous and different pathologies. All these indices can be used as indicators of inflammatory state and severity to evaluate the diagnosis and the clinical prognosis of patients with ES silicosis because, although clinical and radiologic factors may assist in predicting the likelihood of complications and mortality from ES silicosis, evaluating the prognosis of these patients remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…WBC count and its derived indicators such as the neutrophil-to-lymphocyte ratio (NLR) based on the coexistence of lymphopenia and leukocytosis in the initial inflammatory response 17 , 18 , lymphocyte-to-monocyte ratio (LMR) can reflect the body’s immune status, and its decrease indicates host immune dysfunction 19 , platelet-to-lymphocyte ratio (PLR) is an inflammatory marker of immune-mediated, metabolic, prothrombotic, and neoplastic diseases 20 , have been considered as predictors of severity and prognosis of the disease although, by combining several of these parameters, the prediction can be greatly improved. Then, others more inclusive ratios such as: (i) neutrophil x monocyte-to-lymphocyte ratio (systemic inflammation response index or SIRI), which has a stronger stability than NLR and an elevated SIRI suggests increased inflammation and reduced immune response in patients 21 , 22 ; (ii) neutrophil x platelet-to-lymphocyte ratio (systemic immune-inflammation index or SII) with poor prognosis when augmented 23 , 24 and (iii) neutrophil x monocyte x platelet-to-lymphocyte ratio (aggregate index of systemic inflammation or AISI) 25 have been proposed as cheap and easily measurable biomarkers or indicators to improve the diagnosis/prognosis in numerous and different pathologies. All these indices can be used as indicators of inflammatory state and severity to evaluate the diagnosis and the clinical prognosis of patients with ES silicosis because, although clinical and radiologic factors may assist in predicting the likelihood of complications and mortality from ES silicosis, evaluating the prognosis of these patients remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Although AISI represents several inflammatory cells as ingredients and should provide more precise prognostic value, it is rarely used or described in the literature. Most recently, Zinellu et al (2021) underlined its prognostic significance to predict poor outcomes in idiopathic pulmonary fibrosis [ 72 ]. Furthermore, Hamad and coworkers (2021) also studied its importance in patients suffering from COVID-19 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These prognostic scoring systems were different combinations of blood biomarkers. Angelo et al found that AISI was independently associated with IPF, as well as mortality in patients with IPF ( 10 , 11 ). In our study, we combined monocyte with clinical and physiological indicators to predict mortality risk in Chinese patients with IPF.…”
Section: Discussionmentioning
confidence: 99%